Pengaruh Human Relations dan Kondisi Fisik Lingkungan Kerja terhadap Etos Kerja Pegawai Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (BAPPEDA) Kabupaten Bandung - Shelffia Aufa Salshabilla; Rusman Frendika; Allya Roosallyn Assyofa (Bandung Conference Series: Business and Management, 2022)
Abstract. BAPPEDA is a local government agency of Bandung Regency where the workers called State Civil Apparatus have obligations and prohibitions that must be carried out, to carry out their obligations and avoid these prohibitions a high work ethic is required in order to provide the best service to the community as part of their Country duties. Sinamo (2011) explains that there are several factors that influence the formation of a work ethic, including good relations between employees (human relations), the situation and physical condition of the work environment itself, good work security and safety for employees, social conditions of the work environment. , attention to spiritual, physical and self-esteem needs in the work environment, leadership factors, and providing pleasant incentives for employees. This research uses survey method with descriptive analysis method and verification analysis. This type of causal associative research with quantitative data. The population of all BAPPEDA Bandung Regency employees is 52 employees. The sample is 46 employees with purposive sampling technique. Data collection techniques using observation, questionnaires, literature studies, documentation studies. The results obtained are: 1) Human relations at BAPPEDA Bandung Regency is in the good category, 2) The physical condition of the work environment at BAPPEDA Bandung Regency is in the good category, 3) The work ethic of BAPPEDA employees in Bandung Regency is in the good category, 4) The influence of positive and significant human relations on the work ethic of BAPPEDA Bandung Regency employees, 5) The influence of positive and significant physical conditions on the work ethic of BAPPEDA Bandung Regency employees, 6) The influence of human relations and physical conditions of the work environment is positive and significant on work ethic BAPPEDA Bandung Regency employee. Abstrak. BAPPEDA merupakan instansi pemerintah daerah Kabupaten Bandung dimana para pekerjanya yang disebut Aparatur Sipil Negara (ASN) mempunyai kewajiban dan larangan yang harus dilakukan, untuk menjalankan kewajiban dan menghindari larangan tersebut diperlukan etos kerja yang tinggi agar dapat memberikan pelayanan yang terbaik kepada masyarakat sebagai bagian dari tugas Negara. Sinamo (2011) menjelaskan terdapat beberapa faktor yang mempengaruhi terbentuknya etos kerja antara lain hubungan yang terjalin dengan baik antar pegawai (human relations), situasi dan kondisi fisik dari lingkungan kerja itu sendiri, keamanan dan keselamatan kerja yang baik bagi pegawai, keadaan sosial lingkungan kerja, perhatian pada kebutuhan rohani, jasmani maupun harga diri di lingkungan kerja, faktor kepemimpinan, dan pemberian insentif yang menyenangkan bagi pegawai. Penelitian ini menggunakan metode survey dengan metode analisis deskriptif dan analisis verifikatif. Jenis penelitian asosiatif kausal dengan data kuantitatif. Populasi seluruh pegawai BAPPEDA Kabupaten Bandung sebanyak 52 pegawai. Sampel 46 pegawai dengan teknik sampling purposive sampling. Teknik pengumpulan data menggunakan observasi, kuesioner, studi literatur, studi dokumentasi. Hasil penelitian yang diperoleh adalah: 1) Human relations di BAPPEDA Kabupaten Bandung masuk ke dalam kategori baik, 2) Kondisi fisik lingkungan kerja di BAPPEDA Kabupaten Bandung masuk ke dalam kategori baik, 3) Etos kerja pegawai BAPPEDA Kabupaten Bandung masuk ke dalam kategori baik, 4) Pengaruh human relations positif dan signifikan terhadap etos kerja pegawai BAPPEDA Kabupaten Bandung, 5) Pengaruh kondisi fisik lingkunngan kerja positif dan signifikan terhadap etos kerja pegawai BAPPEDA Kabupaten Bandung, 6) Pengaruh human relations dan kondisi fisik lingkungan kerja positif dan signifikan terhadap etos kerja pegawai BAPPEDA Kabupaten Bandung.